2022
DOI: 10.3389/fnut.2022.1091477
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of fat accumulation in 3T3-L1 adipocytes induced by chlorantraniliprole

Abstract: IntroductionChlorantraniliprole is a diamide insecticide widely used in agriculture. Chlorantraniliprole has been previously found to increase the accumulation of triglycerides (fats) in adipocytes, however, the underlying molecular mechanism is unknown. The present study aimed to explore the molecular mechanisms of chlorantraniliprole-induced fat accumulation in 3T3-L1 adipocytes.MethodsWe measured the triglyceride content in chlorantraniliprole-treated 3T3-L1 adipocytes, and collected cell samples treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…3T3L-1 cells differentiated for 24 h, 48 h, 96 h and 8 d were completely digested with Trizol reagent and collected. Total RNA of the samples was extracted without RNase and cDNA libraries were synthesized using the Revert-Aid First Strand cDNA Synthesis Kits as previously reported ( Chen et al, 2022 ; Qi et al, 2022 ). The RT-qPCR was then conducted on a StepOne Plus real-time PCR system.…”
Section: Methodsmentioning
confidence: 99%
“…3T3L-1 cells differentiated for 24 h, 48 h, 96 h and 8 d were completely digested with Trizol reagent and collected. Total RNA of the samples was extracted without RNase and cDNA libraries were synthesized using the Revert-Aid First Strand cDNA Synthesis Kits as previously reported ( Chen et al, 2022 ; Qi et al, 2022 ). The RT-qPCR was then conducted on a StepOne Plus real-time PCR system.…”
Section: Methodsmentioning
confidence: 99%
“…After adding 17 g of water, the mixture was filtered and recrystallized using ethanol to obtain the compound 2-[3-bromo-1-(3-chloro-2-pyridinyl)-1H-5-pyrazol]-6-chloro-8-methyl-4H-benzo [d]. A total of 0.26 mmol of aminobutyric acid and 0.45 mmol of NaOH were added to 5 mL of anhydrous DMF in a 25 mL round-bottomed flask and stirred at 25 [1,3] oxazin-4-one was added. After stirring for 12 h, the solution was mixed with 15 mL of water, adjusted to a pH of 3 using concentrated hydrochloric acid, and then extracted three times with 5 mL of ethyl acetate.…”
Section: Preparation Of Hapten and Antigensmentioning
confidence: 99%
“…Recrystallization with hexane and ethyl acetate (3:1, v/v) produced 80 mg of CAP hapten in 64.7% yield, which was characterized by high-resolution mass spectrometry (HRMS) and nuclear magnetic resonance hydrogen spectroscopy ( 1 H NMR). [1,3] oxazin-4-one was added. After stirring for 12 h, the solution was mixed with 15 mL of water, adjusted to a pH of 3 using concentrated hydrochloric acid, and then extracted three times with 5 mL of ethyl acetate.…”
Section: Preparation Of Hapten and Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse experiments have demonstrated that long-term exposure to CP (18 months) leads to hepatocyte hypertrophy and increased liver weight [11] . Furthermore, a recent study revealed that CP induces adipogenesis in 3T3-L1 adipocytes through the AMP-activated protein kinase α (AMPKα) pathway [12,13] . However, to the best of our knowledge, there are no reports on the effect of CP exposure on obesity or intestinal flora in vivo.…”
Section: Introductionmentioning
confidence: 99%